The Reception of Cicero’s contiones in the 20th and Early 21st Centuries - Kontonasios, Panagiotes (Ciceroniana On Line, 2019)
The paper explores the different approaches taken by 20th and 21st century scholars to Cicero’s extant political speeches before the Roman people (contiones). These speeches offer a resource for Cicero’s views on the role of this political body in the Roman res publica of his time. This study focuses on accounting for the reasons for those differences and how these readings of the contiones underpin diverse portraits of Cicero as an orator and politician. This bibliographic review of contrasting interpretations of the body of contiones helps shed light on why different generations of Cicero scholars and historians of the Roman Republic have judged Cicero as a “consistent” or “inconsistent” orator and politician. This focused bibliographic evaluation leads to a more rounded understanding of Cicero’s personality as portrayed in recent scholarly history and the dimensions this personality has taken on over the period. L’article étudie les approches opposées adoptées par les chercheurs du 20e siècle et du début du 21e siècle, quant aux discours politiques de Cicéron devant le peuples romain (contiones). Ils contiennent les vues de Cicéron sur le rôle de ce corps politique dans la res publica de son temps. Je me concentre sur les raisons mêmes de ces différences et sur la description de Cicéron en tant qu’orateur et homme politique. L’étude bibliographique que j’offre pour les points de vue contrastés clarifie les facteurs qui ont contribué à ces points de vue et éclairent la question de la cohérence ou de l’incohérence de Cicéron en tant qu’orateur et homme politique romain. Tout cela nous mène finalement à une meilleure compréhension de la personnalité de Cicéron et de ses divers impacts dans diverses circonstances historiques.